Grenada : Staff Report for the 2002 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2003)
This 2002 Article IV Consultation highlights that real GDP of Grenada declined by 3 percent in 2001, reflecting the global slowdown, completion of most of the large infrastructure and tourism projects, and the effects on tourism of the September 11 attacks in the United States. The fiscal situation deteriorated markedly in 2001 with the central government deficit rising to 8.5 percent of GDP. For 2002, despite damage to crops and infrastructure caused by a tropical storm in September, economic growth is expected to be slightly positive.